(untitled) (Journal of Hama University, 2019)
The aim of this research is to study the effect of using hCG instead of GnRH in the 2nd injection in the Ovsynch program for estrous synchronization and ovulation Inciting in dairy cows during the anestrus after parturition. In this study, 16 heads of cattle that have been given birth at least once and are not previously observed for estrous and with no signs of deformity are observed in the ovaries. The cattles are randomly divided into two groups (n=8): The first group (experiments group G1) is treated with GPH where it is injected with (100) micrograms of GnRH in day (0) then (500) micrograms in day (7) and (1500) UI hCG in day (9). GPG program is used in the second group (Control group G2) where it is injected with 100 micrograms of GnRH in day (0) then (100) micrograms of GnRH in day (9). An ultrasound exam is performed in day (9-10) to detect the ovulation and determine its time, then an artificial insemination is performed 24 hour after the second injection of GnRh/hCG. The pregnancy is diagnosed (35) days after the insemination then it is repeated after (90) days. The results show no significant differences (p<0.05) between the cattles of the two groups with regard to the diameter of the follicle before the ovulation, while there is a significant difference (p>0.05) in the ovulation rate (87.5% - 62.5%)GPH and GPG Respectively, where improvement was observed in pregnancy rates between the two groups (62.5% - 37.5%). The study concluds the importance of using hCG instead of GnRh in the Ovsynch program to increase ovulation rates and improve the pregnancy rates.